Surgical management of horizontally impacted mandibular canine in a 10 years old child - Singh, Aparna; Shikh, Smriti; Sagarika,; Kumar, Arvind; Dipti, Nehal; Ghosh, Debadyuti (International Journal of Research in Medical Sciences, 2025)
Impacted tooth refers to a tooth that fails to erupt into the dental arch within a specific time. Teeth frequently impacted are-third molars, maxillary canines, maxillary and mandibular premolars and maxillary central incisors. Failure of eruption of the mandibular canine is an unusual event. It has been suggested that eruption disturbances of a mandibular canine are most often caused by local factors such as mechanical obstruction (supernumerary tooth/cyst/tumour), insufficient space in the dental arch and tooth-arch size discrepancy. This case report presents surgical management of an impacted permanent mandibular canine of a 10 years old boy under local anaesthesia.